The Financing of Drug Trials by Pharmaceutical Companies and Its Consequences: Part 2: A Qualitative, Systematic Review of the Literature on Possible Influences on Authorship, Access to Trial Data, and Trial Registration and Publication - Schott, Gisela (Deutscher Arzte Verlag, 2010)
BACKGROUND: In recent years, a number of studies have shown that clinical drug trials financed by pharmaceutical companies yield favorable results for company products more often than independent trials do. Moreover, pharmaceutical companies have been found to influence drug trials in various ways. This overview of current, systematic studies on this topic is intended to identify and characterize the particular aspects of the performance of a drug trial that can be affected by financial support from a pharmaceutical company. METHODS: Publications retrieved from a systematic Medline search on this topic from 1 November 2002 to 16 December 2009 were independently evaluated and selected by two of the authors. These publications were supplemented by further ones found in their references sections. RESULTS: 57 publications were included for evaluation in Parts 1 and 2 of this article. A number of studies revealed that many trials financed by pharmaceutical companies—in some cases, as many as half of all such trials—are never published. Moreover, multiple publications of the same findings were found, and some reports were found to include selectively published data. Further studies revealed evidence of other problems including incomplete trial registration, constraints on publishing rights, withheld knowledge of adverse drug reactions, and the use of ghostwriters who were supplied by the pharmaceutical companies. CONCLUSION: Financial support from a pharmaceutical company influences multiple aspects of the performance of drug trials and often leads to a favorable result for the corporate sponsor of the trial. Public access to trial protocols and results must be ensured. Moreover, more effort should be made to carry out drug trials independently, without the financial support of pharmaceutical companies.